DINAMIKA PERTUMBUHAN PENDUDUK DAN KUALITAS AIR DI INDONESIA - Kustanto, Andi (Jurnal Ilmu Ekonomi dan Pembangunan, 2020)
Population growth and urban development continue to increase at an unprecedented rate and create pressure on the quality of clean water. Previous empirical studies have shown that un-controlled population growth has a negative and significant impact on the quality of clean water. In the case of Indonesia, the population growth trend has decreased every year, but not followed by an index of water quality that should have increased. This study examines popula-tion growth in the water quality index in 33 provinces in Indonesia during 2013-2017 using the panel method of fixed-effect models. This study found that population growth has a nega-tive and significant effect on the water quality index in Indonesia. Every 1000 population in-crease will reduce the water quality index by 0.04 (ceteris paribus), which indicates that there is a need for control of the population growth rate to be more aware of the preservation of a sustainable environment.Keywords: Population Growth, Water Quality Index, Environment